Development of a new ERA-CRISPR/Cas12a method for rapid sensitive detection of Ralstonia pseudosolanacearum in eucalyptus - Peng, Xiaoping; Wang, Shengkun; Zhang, Yipin; Wang, Shengjie; Meng, Sen; Hu, Lipan; Ma, Haibin (Frontiers in Plant Science, 2025)
IntroductionRalstonia pseudosolanacearum is a significant pathogenic bacterium that causes bacterial wilt in Eucalyptus worldwide. Asymptomatic Eucalyptus cuttings may harbor substantial quantities of R. pseudosolanacearum, leading to latent infections that increase the risk of pathogen dissemination. Currently, there are no effective methods available to cure Eucalyptus bacterial wilt; therefore, rapid and sensitive detection methods for this disease are urgently needed to mitigate losses in the Eucalyptus industry.MethodsIn this study, we developed a rapid and accurate diagnostic method for detecting R. pseudosolanacearum based on enzymatic recombinase amplification (ERA) combined with clustered regularly interspaced short palindromic repeats (CRISPR)/Cas12a technology.ResultsThe ERA-CRISPR/Cas12a method demonstrated high specificity and exhibited no cross-reactivity with other common bacterial pathogens. The detection limit for R. pseudosolanacearum by the fluorescence and the LFS detection system was as low as 100 copies/µL. Furthermore, the results can be visualized through an ERA-CRISPR/Cas12a fluorescent signal (ERA-CRISPR/Cas12a-FL), color under blue light or an ERA-CRISPR/Cas12a lateral flow strip (ERA-CRISPR/Cas12a-LFS).DiscussionThe newly developed ERA-CRISPR/Cas12a method could detect R. pseudosolanacearum in Eucalyptus rapidly and accurately. Moreover, the samples can be detected within one hour by our developed method, highlighting the significant potential for onsite applications in disease management.